Training of Business Prospects for Ornamental Plants and Superior Fruit Nursing: Study of Development of Self Tourism Village Based on Agricultural Economy - Suparno; Saptono, Ari; M., Saparuddin; Iranto, Dicky; N., Sri Indah; Sariwulan, Tuty; Sofwan, M.; Putri, Indira (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2023)
Community Service this training on business prospects for ornamental plants and superior fruit nurseries was carried out in Cisaat village, Sukabumi-Subang sub-district, where some tourist villages have superior ornamental plants and superior fruit that can be cultivated. Utilization of fertile land can be increased so that it becomes a potential agro-business tourism to be developed and become a superior product. This community service also provides business analysis training. The competencies obtained in this community service are 1. Farmers can select and produce superior seeds, 2. Farmers are able to develop nurseries with various media, 3. Farmers can develop nurseries by utilizing agricultural land, 4. Farmers can analyze production costs and business prospects. The method implemented is in the form of training with people who own land but it is not used optimally, as well as ornamental and fruit plant farmers. With training on business prospects, development of superior ornamental and fruit plants. Provision of seeds so that further development can be carried out for farmers. The next hope is that farmers will be able to produce superior ornamental plants and fruit in tourist villages with BumDes.